DIFFERENT LEGISLATIONS REGARDING OPAs (Artículo publicado en inglés) (Estudios Gerenciales, 2004)
An analysis was made of then effectof the Tender Offer Law in Chile, andof the related situation of five countrieswith a more developed marketthan the Chilean one, reaching theconclusion that in order to successfullyimplement a Tender Offer Lawit is necessary to bear in mind thatthe problem is not solved by establishingstandards that regulate transactions,but by creating instancesthat contribute to a more dynamicand efficient market. In addition,there should exist a balance betweenprotection of the minority stockholderand competition for corporate control.Finally, we can conclude that thereis evidence that the Tender Offer Lawhas depressed the Stock Exchange.